2023
DOI: 10.1111/psyp.14272
|View full text |Cite
|
Sign up to set email alerts
|

Event‐related potentials associated with attentional networks evidence changes in executive and arousal vigilance

Abstract: Attention is regulated by three independent but interacting networks, that is, alerting, comprising phasic alertness and vigilance, orienting, and executive control. Previous studies analyzing event‐related potentials (ERPs) associated with attentional networks have focused on phasic alertness, orienting, and executive control, without an independent measure of vigilance. ERPs associated with vigilance have been instead measured in separate studies and via different tasks. The present study aimed to differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 117 publications
(283 reference statements)
2
8
2
Order By: Relevance
“…Polynomial contrasts demonstrated a significant and negative linear component for hits across blocks [t (34) = −5.23, p < 0.001, η 2 p = 0.45, CI 95% (0.24, 1.00)]. Unexpectedly, however, the AV decrement was not observed in the present study and Luna et al (2023) (see Figure 2B): the change of mean RT across blocks was not significant [F (3.93,133.78) = 0.46, p = 0.764, η 2 p = 0.01, CI 95% (0.00, 0.03)]. A summary of EV and AV overall performance is presented in Table 1.…”
Section: Behavioral Performancecontrasting
confidence: 73%
See 4 more Smart Citations
“…Polynomial contrasts demonstrated a significant and negative linear component for hits across blocks [t (34) = −5.23, p < 0.001, η 2 p = 0.45, CI 95% (0.24, 1.00)]. Unexpectedly, however, the AV decrement was not observed in the present study and Luna et al (2023) (see Figure 2B): the change of mean RT across blocks was not significant [F (3.93,133.78) = 0.46, p = 0.764, η 2 p = 0.01, CI 95% (0.00, 0.03)]. A summary of EV and AV overall performance is presented in Table 1.…”
Section: Behavioral Performancecontrasting
confidence: 73%
“…As reported in Luna et al (2023) and similarly to previous studies with the ANTI-Vea (Luna et al, 2018(Luna et al, , 2021a, the EV decrement was observed as a significant change in hits across time-on-task [F (4.55,154.58) = 9.70, p < 0.001, η 2 p = 0.22, CI 95% (0.11, 0.30); see Figure 2A]. Polynomial contrasts demonstrated a significant and negative linear component for hits across blocks [t (34) = −5.23, p < 0.001, η 2 p = 0.45, CI 95% (0.24, 1.00)].…”
Section: Behavioral Performancesupporting
confidence: 54%
See 3 more Smart Citations